2009
DOI: 10.5194/acp-9-677-2009
|View full text |Cite
|
Sign up to set email alerts
|

Scaling behaviour of the global tropopause

Abstract: Abstract. Detrended fluctuation analysis is applied to the time series of the global tropopause height derived from the 1980-2004 daily radiosonde data, in order to detect longrange correlations in its time evolution.Global tropopause height fluctuations in small timeintervals are found to be positively correlated to those in larger time intervals in a power-law fashion. The exponent of this dependence is larger in the tropics than in the middle and high latitudes in both hemispheres. Greater persistence is ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…In contrast, volcanic eruptions cool the surface, but aerosol heating warms the sunlit lower stratosphere (Shindell et al, 2003;Miller et al, 2012). This leads to an increased meridional gradient in the lower stratosphere but a reduced gradient in the tropopause region (Chandra et al, 1996;Varotsos et al, 1994Varotsos et al, , 2009. Vyushin et al (2004) suggested that volcanic forcings improve the low-frequency variability scaling performance of atmosphere-ocean models compared to all other forcings (see, however, the comment by Blender and Fraedrich, 2004, which also discusses earlier papers on the field) and Blender and Fraedrich (2004).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, volcanic eruptions cool the surface, but aerosol heating warms the sunlit lower stratosphere (Shindell et al, 2003;Miller et al, 2012). This leads to an increased meridional gradient in the lower stratosphere but a reduced gradient in the tropopause region (Chandra et al, 1996;Varotsos et al, 1994Varotsos et al, , 2009. Vyushin et al (2004) suggested that volcanic forcings improve the low-frequency variability scaling performance of atmosphere-ocean models compared to all other forcings (see, however, the comment by Blender and Fraedrich, 2004, which also discusses earlier papers on the field) and Blender and Fraedrich (2004).…”
Section: Discussionmentioning
confidence: 99%
“…El Niño/La Niña Southern Oscillation (ENSO) is an oceanicatmospheric quasi-periodic phenomenon with several impacts on climate and weather not only in the tropical Pacific, but in many regions all over the world (Varotsos and Deligiorgi, 1991;Kondratyev and Varotsos, 1995a, b;Klein et al, 1999;Xue et al, 2000;Eccles and Tziperman, 2004;Varotsos, 2007, 2011;Lin, 2007;Chattopadhyay and Chattopadhyay, 2011;Efstathiou et al, 1998Efstathiou et al, , 2011Varotsos, 2013;C. Varotsos et al, 2009C.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study is important in view of the stratospheric ozone thinning scenario (Tolba and Osama 1992). Some studies (Varotsos et al 2004(Varotsos et al , 2008Varotsos, Efstathiou, and Tzanis 2009) explained the inverse relationship between column ozone and TH at various geographical sites, showed a longitudinal and latitudinal variability and also analysed the TH variability reducing the existing uncertainties in assessing the climatic characteristics. The decreasing trend in the ozone of this Figure 4.…”
Section: Resultsmentioning
confidence: 99%